Adiponectin: From obesity to cardiovascular disease: Etiology and Pathophysiology - Antoniades, C; Antonopoulos, A; Tousoulis, D; Stefanadis, C (2009)
Adiponectin is an adipokine whose biosynthesis is deranged in obesity and diabetes mellitus, predisposing to atherosclerosis. Evidence suggests that adiponectin has anti-atherogenic properties by improving endothelial function and having anti-inflammatory effects in the vascular wall. In addition, adiponectin modifies vascular intracellular redox signalling and exerts indirect antioxidant effects on human myocardium. However, its clinical role in cardiovascular disease is obscure. Adiponectin's positive prognostic value in coronary artery disease had been widely supported over the last years, but this view has been questioned recently. High adiponectin levels are paradoxically associated with poorer prognosis in heart failure syndrome. These controversial findings seem surprising as adiponectin has been viewed overall as an anti-atherogenic molecule. Therefore, any certain conclusion about adiponectin's role in cardiovascular disease seems premature. Despite the rapidly accumulating literature on this adipokine, it is still unclear whether adiponectin is a key mediator or a bystander in cardiovascular disease. It is still uncertain whether adiponectin levels have any clinical significance for risk stratification in cardiovascular disease or they just reflect the activation of complex and opposing underlying mechanisms. Circulating adiponectin levels should be interpreted with caution, as they may have completely different prognostic value, depending on the underlying disease state. © 2009 International Association for the Study of Obesity.